ANALISIS USER INTERFACE PADA APLIKASI PERPUSTAKAAN DIGITAL iJAKARTA - Hanifa, Salsabila; Masruri, Anis; Sari, Kartika Putri (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2023)
The purpose of this research discusses the user interface analysis of the iJakarta digital library application as an innovation from the conventional library form into a digital library form. The iJakarta application was developed by the DKI Jakarta Provincial Government under the auspices of the DKI Jakarta Regional Library and Archives Agency (BPAD) for residents in the DKI Jakarta area and all Indonesian people. The research method uses qualitative research with a case study approach, namely revealing the actual data and describing the existing conditions in the field and examining the phenomena that occur which focus on a person's life experience. The results showed that: the user interface on the iJakarta digital library application has met the requirements of the main components, namely: 1) color, the color selection in the iJakarta application uses orange, this gives a warm impression, 2) font, the iJakarta application uses Arial font on a book reading in it using Times New Roman font, 3) navigation, namely the location of icons and buttons in the application that makes it easier for iJakarta users to search for information, 4) icons, which are characteristics of an application so that users can immediately remember that the icon is one of the applications and can shorten user interaction because it is very easy to recognize, 5) buttons, the use of buttons is almost the same as icons, easy to recognize and shorten user interactionKeywords: Application, Digital Library, iJakarta , User Interface